Dutch and Indonesian teachers on teaching medical ethics: what are the learning goals?. Issue 1 (31st December 2022) - Muhaimin, Amalia; Hoogsteyns, Maartje; Lestari, Diyah Woro Dwi; Ferine, Miko; Utarini, Adi; Willems, Derk Ludolf
ABSTRACT: Previous literature has discussed the different views, the diverse goals and scope of ethics education, and the need for a more homogenous curriculum in medical ethics. Since ethics is about values, and values are partly influenced by culture, we question to what extent teachers' perceptions concerning learning goals of medical ethics curricula are similar or different in two different countries, and if differences in learning goals are acceptable or problematic. We conducted in-depth interviews with 36 medical ethics teachers, 20 from Indonesia and 16 from the Netherlands, and explored what they think are the important learning goals. We found three similar goals, with slightly different perceptions, between the two groups: (1) being professional, (2) dealing with ethical problems, and (3) being part of society. We also found four other goals that differed between the two countries: (4) understanding one-self and (5) learning from others from the Netherlands; (6) being faithful/pious and (7) obeying rules/standards from Indonesia. We suggest that despite similar goals shared globally, there might be differences in how teachers in different cultural contexts perceive the goals with their local values and translate them into the curricula. Differences in learning goals are common and natural, often reflected by historical and sociocultural contexts, and should not become a barrier for teachers in different regions to collaborate. Understanding these differences may be an important goal for teachers themselves to broaden their knowledge and perspectives.